The Effectiveness of History Learning in Character Building of Grade 2A Students at SMA 2 Palu - Abdul Wahid Dg. Napu; Juraid Juraid; Iskandar Iskandar; Fajar Nugroho; Minarni Nongtji (FKIP - Universitas Riau, 2026)
This study aims to analyze the role of history teachers in shaping the character of students in class 2A at SMA Negeri 2 Palu and to identify the obstacles encountered in the process. The study uses a qualitative approach with a phenomenological method to understand the experiences of teachers and students regarding the effectiveness of history learning in instilling character values. Data collection techniques included observation, in-depth interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that history learning was effective in shaping student character when the material was integrated with moral values such as discipline, responsibility, religiosity, nationalism, honesty, and social awareness. The strategies used by teachers included emphasizing discipline, setting an example, religious habits, group discussions, the use of visual media, and the proportional giving of rewards and punishments. The school's support through learning facilities also strengthened the process of internalizing values. Despite challenges in the form of environmental influences and the negative behavior of some students, history learning was proven to contribute significantly to shaping students' positive attitudes, responsibility, and national awareness.